La terapia centrada en esquemas de Jeffrey Young - Rodríguez Vílchez, Edgar (2009)
Scheme therapy is an integrated psychotherapy which mixes elements from cognitive and behavior therapy, Attachment theory, Gestalt, constructivist and dynamic elements. Young has developed the Scheme therapy during the last 20 years, from the casuistic of the ones who share his approaches. The Scheme therapy comes up as a good alternative to those patients who suffers consolidated chronic psychological disorders, considered difficult to treat, including patientswith TP and those who have significant characterological aspects that constitute the disorder basis of Axis 1 Disorders.